Effect of aluminate and carbonate in magnesia silicate cement. (May 2023) - Bernard, Ellina; Lothenbach, Barbara; German, Alexander; Rentsch, Daniel; Winnefeld, Frank
Abstract: The effect of alumina and carbonates on magnesium silicate hydrate (M-S-H) cements was investigated at high Mg/Si ratios (1.5–2.5), constant Na2 CO3 concentration (17 g/L) and Al/Si ratio of either 0, 1 or 3.2. Either MgO or MgO/hydromagnesite (50/50 wt %) was used, as well as silica fume, metakaolin or amorphous Al2 O3 . Thermogravimetric analysis (TGA), X-ray diffraction (XRD), 29 Si and 27 Al MAS NMR data showed that M-(A-)S–H phases formed in all cases and hydrotalcite in presence of aluminum. Little hydromagnesite had reacted in the presence of aluminum. The 23 Na MAS NMR data showed that only little sodium was sorbed; the thermogravimetric analysis coupled with infrared exhaust gas analysis and 13  C MAS NMR data showed that carbonates were incorporated in the hydrotalcite and traces of carbonate were sorbed. Thermodynamic modelling carried out with an updated Mg-phases database was in relatively good agreement with the phase assemblage observed if the reactivity of the starting materials was considered.